2018
DOI: 10.1111/tbed.12897
|View full text |Cite
|
Sign up to set email alerts
|

Detection of vaccine-like lumpy skin disease virus in cattle and Musca domestica L. flies in an outbreak of lumpy skin disease in Russia in 2017

Abstract: Since 2012, lumpy skin disease virus (LSDV) has been spreading from the Middle East to south-east Europe and Russia. Although vaccination campaigns have managed to contain LSDV outbreaks, the risk of further spread is still high. The most likely route of LSDV transmission in short distance spread is vector-borne. Several arthropod species have been suggested as potential vectors, but no proven vector has yet been identified. To check whether promiscuous-landing synanthropic flies such as the common housefly (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 22 publications
5
69
1
2
Order By: Relevance
“…As described in this study, since the GPCR locus of all isolates from 2018 carried the unique CTCAGTACAATT indel, they all tested positive for the vaccine strain in the assay developed by Agianniotaki et al [42]. They were negative for a LSDV vaccine signature in LSDV008 using a PCR, which only detects commercial LSDV vaccine isolates [27].…”
Section: Plos Onementioning
confidence: 60%
“…As described in this study, since the GPCR locus of all isolates from 2018 carried the unique CTCAGTACAATT indel, they all tested positive for the vaccine strain in the assay developed by Agianniotaki et al [42]. They were negative for a LSDV vaccine signature in LSDV008 using a PCR, which only detects commercial LSDV vaccine isolates [27].…”
Section: Plos Onementioning
confidence: 60%
“…Both types of clinical presentation were positive by PCR and VI in lymph nodes, and the affected internal organs were for DNA and infectious virus in clinically ill animals ( insects merit further investigation for their potential role in mechanical transmission. Muscidae flies have been implicated in carrying a vaccine-like LSDV that causes outbreaks of the generalized form (Sprygin, Pestova, Prutnikov, & Kononov, 2018). Moreover, the nonblood-sucking fly, Musca autumnalis, possesses prestomal teeth to rasp away the conjuctiva to stimulate the flow of tears (Giangaspero & Broce, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Role of Stomoxys calcitrans as a vector of lumpy skin disease was investigated in several studies, which showed high potential of S.calcitrans for virus transmission [11][12][13]. The role of Musca domestica as a vector of LSDV is not yet clear, but case of detection of virus in M.domestica samples indicates its potential for mechanical transmission [14]. PCR protocol was effective for detection of LSDV genome in infected tissue cultures.…”
Section: Discussionmentioning
confidence: 99%